Citizens' Solidarity in Europe: Civic Engagement and Public Discourse in Times of Crises - Christian Lahusen (Edward Elgar Publishing, 2020)
Citizens' Solidarity in Europe systematically dissects the manifestations of solidarity buried beneath the official policies and measures of public authority in Europe. In this exciting and innovative book, contributors offer comprehensive and original data and highlight the detrimental factors that tend to inhibit or annihilate solidarity, and those that are beneficial for the nurturing of solidarity.